1972
DOI: 10.1111/j.1467-6494.1972.tb00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying intensity of attack and fear arousal on the intensity of counter aggression 1

Abstract: A provocative but little studied hypothesis in research on aggression is the notion that Assummg equal hahit strength for both fli^t and fight, and assummg that tiie attacker and the victim are of equal status, the tendency to coimter-attack should vary curvihnearly with the mtensity of attack Tins relationship is especially apparent when the attack consists of physical aggression. (Buss, 1961, P 29) Buss explains that if physical attack is very mild, it serves as a weak stimulus for counter aggression. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Indeed, only a small number of experiments have sought to examine the aggression-inhibiting influence of threatened punishment, and even the fmdings of these studies have been somewhat inconclusive. Thus, while several recent investigations have reported that threatened punishment is indeed effective in inhibiting human aggression (e.g., Baron, 1971;Shortell , Epstein , & Taylor, 1970), other experiments have failed to substantiate the occurrence of such effects (Baron, 1973;Knott & Drost, 1972) . The inconsistent findings of these studies, coupled with the informal observation that threatened punishment sometimes succeeds, and sometimes fails in inhibiting overt aggression in various situations outside the laboratory, suggest very strongly that the influence of this variable is mediated by several additional factors .…”
mentioning
confidence: 94%
“…Indeed, only a small number of experiments have sought to examine the aggression-inhibiting influence of threatened punishment, and even the fmdings of these studies have been somewhat inconclusive. Thus, while several recent investigations have reported that threatened punishment is indeed effective in inhibiting human aggression (e.g., Baron, 1971;Shortell , Epstein , & Taylor, 1970), other experiments have failed to substantiate the occurrence of such effects (Baron, 1973;Knott & Drost, 1972) . The inconsistent findings of these studies, coupled with the informal observation that threatened punishment sometimes succeeds, and sometimes fails in inhibiting overt aggression in various situations outside the laboratory, suggest very strongly that the influence of this variable is mediated by several additional factors .…”
mentioning
confidence: 94%